A rare case of conjunctival malignant melanoma with orbital invasion - Rajbhandari, Yogita; Gupta, Sharad; Yadav, Reena; Manandhar, Ashma; Mon, Aye Myat; Joshi, Pramiti; Shrestha, Gulshan Bahadur (Nepalese Journal of Ophthalmology, 2019)
Background: Conjunctival malignant melanoma is a rare ocular malignancy most commonly affecting mostly the elderly population. It is a pigmented lesion which canarise from primary acquired melanosis, de novo or from preexisting nevus. Case: A 63 year old male presented with a chief complaints rapidly increasing mass in the left eye for two months following trauma with a wooden stick. He had preexisting nevus in the same eye. His best corrected visual acuity was 6/12 in right eye and 1/60 left eye respectively. Slit lamp biomicroscopy examination showed 4 cm x 4 cm pigmented mass in the nasal bulbar and inferior palpebral conjunctiva causing mechanical ectropion of the lower lid with keratinization of palpebral conjunctiva. Incisionalbiopsy of conjunctiva showed malignant melanoma. On computed tomography, there was expansion of bony orbit. Considering all the findings, exenteration of the left orbitwas done. Histopathological report of exenterated mass was suggestive of malignantmelanoma of conjunctiva. Conclusion: Conjunctival melanoma is a rare malignant tumor of eye which has high metastasis rate and the treatment option is surgery with adjuvant therapy.